Adjacency and locality: A constraint-based analysis of complementizer-adjacent ex- traction - Asudeh, A (CSLI Publications, 2009)
This paper provides a new explanation of phenomena related to extraction following an overt complementizer (‘that-t effects’), for which the theory-neutral term complement-adjacent extraction is adopted. The analysis stems from the Correspondence Architecture of Lexical-Functional Grammar, making formally explicit certain implicit, native relations of the architecture. No reference is made to traces. The key insight is that complement-adjacent extraction effects concern linear string adjacency, where the string is understood as part of the syntax–phonology interface. A new metavariable, ≻, is introduced and formally defined; ≻ identifies the next word’s f-structure. A single constraint is proposed that accounts for a wide range of relevant phenomena